Vigorous replication strategy with balanced quorum for minimizing the storage consumption and response time in cloud environments - Mohd Ali, Fazlina; Latip, Rohaya; Alrshah, Mohamed A.; Abdullah, Azizol; Ibrahim, Hamidah (IEEE, 2021)
Digital data is establishing enormously across the globe, which is considered highly valuable due to its significant contributions to facilitate different individuals’ lives. Even though technology evolving rapidly, data availability remains a major challenge due to the heterogeneity of the data with different types, platforms, and technologies. Additionally, the acquired data must be always available and accessible for users regardless of time and location, which appears to be another crucial issue due to many inefficient system implementations. The most essential option to solve this issue is by providing the best replication strategies that are able to afford business continuity without interruption. Essentially, cloud replication must be able to secure huge data by enabling comprehensive replication strategies, optimal data availability, fast data retrieval, and cost-effective data management and maintenance. Therefore, this paper mainly introduces the Vigorous Replication Strategy with Balanced Quorum (VRS-BQ) replica placement technique for minimizing storage consumption, response time and replication process time in cloud environments. Comprehensive experiments have been conducted using the well-known CloudSim simulation tool, in which the results reveal that the proposed VRS-BQ algorithm attains 25% lower average response time, 22% lower replication time, and 20% lower storage consumption compared to the existing DPRS algorithm while maintaining a high level of data availability.